Methods and receptions of prosecution of texts on the lesson of Chinese (Journal of Oriental Studies, 2016)
Methods of the work are researched In article with text. They are considered purposes and problems persecuted when work with text and are analyzed different types of the text tasks.
Keywords: period of work with text; types of works with text; methods of works with text.